Mindfulness dan Kreativitas Karyawan Gen Z: Menguji Peran Moderasi Dukungan Supervisor untuk Kreativitas - Rizka Fatkhin Nisa; Stevi Jimry Poluan; Sari Wijayanti (MAMEN: Jurnal Manajemen, 2026)
Generation Z has now entered the workforce and is one of the generations known for its creativity and concern for mental well-being. This study examines the effect of mindfulness on the creativity of Generation Z employees based on resource conservation theory. In addition, this study examines the moderating role of supervisor support for creativity in the effect of mindfulness on the creativity of Generation Z employees based on self-determination theory. This study uses a quantitative research design with primary data from 100 Generation Z employees, collected using questionnaires and analysed using Smart-PLS 4.0. The results of the analysis show that mindfulness has a direct effect on the creativity of Generation Z employees. However, supervisor support for creativity does not moderate the effect of mindfulness on the creativity of Generation Z employees. These results indicate that Generation Z’s creativity does not fully depend on the direct role of supervisors, as this generation’s characteristics as digital natives emphasize flexibility, autonomy, and the use of technology and digital resources to accomplish tasks and express ideas independently.